2018
DOI: 10.1177/0093650218796371
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Quality of Social Support Messages Produced Online: The Role of Responsibility for Distress and Others’ Support Attempts

Abstract: Brunswik’s lens model was used as a guide to investigate the conditions under which people produce more and less effective support messages online. An experiment was conducted to examine the effects of identity cues concerning a support seeker’s responsibility for his or her distress and behavioral residue involving other online community members’ responses to the support seeker. Participants evaluated the support seeker more negatively, produced support messages containing lower levels of person-centeredness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Conversely, when the authenticity of a help-seeking message is doubted in the responses of others, recipients would perceive seekers' requests as illegitimate and leave unconstructive messages. 68 In alignment with Li and Feng's 67 insights, another prior contextual factor, situational severity, can also play a similar role conferring legitimacy during a health crisis. Several studies 69,70 on newsframes of SARS in China found that increased epidemic severity increases news coverage of symptoms, protective measures, and medical resources.…”
Section: Prior Contextual Factorsmentioning
confidence: 83%
See 2 more Smart Citations
“…Conversely, when the authenticity of a help-seeking message is doubted in the responses of others, recipients would perceive seekers' requests as illegitimate and leave unconstructive messages. 68 In alignment with Li and Feng's 67 insights, another prior contextual factor, situational severity, can also play a similar role conferring legitimacy during a health crisis. Several studies 69,70 on newsframes of SARS in China found that increased epidemic severity increases news coverage of symptoms, protective measures, and medical resources.…”
Section: Prior Contextual Factorsmentioning
confidence: 83%
“…One possible explanation could be social compensation. Earlier experimental studies 67,68 have found that even if the profile of a support seeker does not have clear, credible, and identifiable cues, support givers tend to perceive the support seeker to be more trustworthy if there exist credible supporters and positive supporter comments. Social media can offer account information about users who reposted support seeking messages earlier (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is a growing body of research on online‐mediated disclosure, affordances of such communication, and support provision (e.g., Rains et al, 2019), self‐related factors warrant further investigation in this context. Self‐efficacy, that is the belief in one's ability to provide support (Bandura, 1977), although a complimentary body of work in terms of facilitating or hindering helping behavior, has not been as well explored in relation to online support provision.…”
Section: Introductionmentioning
confidence: 99%
“…mental health: therapy, (8) family, (9) marriage, (10) activity scheduling, 11physical attractiveness, (12) dating, (13) finances, (14) food/eating preparation, Feng et al, 2016;Rains et al, 2018). Cohen and Wills (1985) previously noted the need for more diverse samples with greater variabilities of stress and support.…”
Section: Topics Identifiedmentioning
confidence: 99%